#288 : Comparison of OVOIL and OVOIL HEAVY in the Clinical IVF Laboratory on Fertilization, Blastocyst Utilization and Transfer Outcomes - H Kathryn Gurner; R.L Kelley; Y.S Lee; D.K Gardner (Fertility & Reproduction, 2023)
Background and Aims: OVOIL HEAVY (Hv-OIL, Vitrolife) is a new synthetic oil, which compared to a paraffin oil OVOIL, has increased viscosity which may benefit handling, and provide osmolality and pH stabilisation. Being synthetically derived, Hv-OIL may reduce risk of impurities/contaminants. The manufacturer reports that Hv-OIL improves mouse and human embryo development1. The aim of this study was therefore to compare the effect of Hv-OIL vs OVOIL on IVF/ICSI cycle outcomes. Method: OVOIL and Hv-OIL were used across alternating fortnights for all patients in one laboratory between June 2022 and March 2023 (n=1,116 patients). Donor-recipient, egg thaw and egg freeze cycles were excluded. Embryos were cultured in G-TL media (Vitrolife) under 6.5% CO2, 5% O2 in an Embryoscope+. Results: Hv-OIL (n=554) had no effect on fertilisation rate compared to OVOIL (n=562) following either IVF (53.9% vs 55.1%) or ICSI (61.2% vs 60.5%). Utilisation rate per 2PN was similarly unaffected by oil type (51.2%± 0.01 vs 48.2%± 0.02), and this was unchanged by method of insemination. Hv-Oil had no impact on blastocyst development rate compared to OvOil (64.2 vs 61.5%), and the number of top-quality blastocysts (Gardner grade 4/5AA) per 2PN was not different (14.5% vs 16.6%). Positive hCG (46.52% vs 50.1%), fetal heart (27% vs 32%) and fetal sac (31% vs 36%) rate from fresh, single Day 5 transfers was not different between Hv-Oil (n=210 ETs) and OvOil (n=230 ETs) respectively. Osmolality of culture media in Embryoscope+ slides was not different following 7 days of incubation in either oil. Conclusion: There were no observed differences in fresh cycle outcomes with use of Hv-OIL as an oil overlay. However, the impact of Hv-OIL on live birth and FET outcomes, specific patient populations or use in different types of culture systems remains to be evaluated.